REKRUTMEN KARYAWAN BARU BERBASIS METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Dona Kurnia (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2021)
The decision support system  of  the recruitment of new employees. Method that can be used is the Analytical Hierarchy Process (AHP) method where the new employee recruitment process with the AHP method aims to assist managers in making decisions in the new employee selection process by presenting alternatives that are displayed in the form of an alternative ranking system. In this journal a case study was conducted at PT. Bukittinggi City Cellular Business Partner which is currently in the process of recruiting new employees. The analytical method used is the System Development Life Cycle (SDLC)  from the registration process for new employees to the selection process for new employee recruitment. To make it easier for managers to make decisions on the selection of new employee recruitment with the AHP method, so that it will produce really qualified employees. Recruitment of new employees uses 4 criteria, namely administration, knowledge, psychotest and interview with CR = 0.01 which shows the criteria are acceptable because the results shown are CR <10%. The analysis was carried out on 5 samples of new employee candidates which resulted in a ranking where candidate 3 obtained the highest score of 0.28. After the testing process was carried out with a new employee recruitment application using the AHP which was applied to 5 new employee candidates, it showed that the system could be categorized in good condition used for decision making by managers in the new employee selection process.